HUBUNGAN AKTIVITAS FISIK DENGAN KUALITAS HIDUP PEREMPUAN MENOPAUSE - Umi Azizah Kusumaningrum; Rina Nur Hidayati (Universitas Pesantren Tinggi Darul Ulum, 2022)
Menopause is a condition where a woman is no longer has a menstrual cycle. There are changes in both physical and psychological condition that affects the life of these menopousal women at various aspects, one is dealing with the aging process which has an impact on increasing physical, mental and social disorders that have an impact on their quality of life. Various efforts can be made to overcome the symptoms and complaints that occurs in menopousal women, one of which is by maintaining physical activity. The purpose of this study is to determine the relationship between physical activity and quality of life in women with menopause. The population of this study are the elderly people in the Peterongan Jombang Health Center Area. This study uses purposive sampling to obtain samples according to eligibility criteria and obtained 70 respondents. The measuring instrument to identify physical activity used the PASE (Physical Activities Scale For Elderly) questionnaire, while the respondent's quality of life was measured using the WHOQOL (The World Health Organization of Quality of Life Instrument) questionnaire. Data analysis to determine the relationship between the two variables used the Spearman Rho test with a meaning level of 95% (?=0.05). Based on the results of the study, most respondents (49%) had moderate physical activity and most respondents (54%) had poor quality of life. The results of data analysis obtained a p-value of 0.004 (<0.05) which means that there is a relationship between physical activity and quality of life in menopausal women in the Peterongan Jombang Health Center Area. Quality of life is closely related to the severity of menopausal symptoms and physical activity. The better physical activity is done the higher the quality of life to be. Keywords: Physical activity, Quality of life, Menopause